Human health risk assessment for consumption of microplastics and plasticizing substances through marine species - Montero-Campos, Virginia; Chinchilla, Yarenis; Gómez, Luis; Flores, Adrián; Medaglia, Alejandro; Guillén, Rossy; Montero, Ernesto (Instituto Tecnológico de Costa Rica, 2023)
Conferencia: Human health risk assessment for consumption of microplasticsand plasticizing substances through marine species, presentada por Virginia Montero, Yarenis Chinchilla, Luis Gómez, Adrián Flores, Alejandro Medaglia, Rossy Guillén, Ernesto Montero, en el año 2023
Conferencia. Instituto Tecnológico de Costa Rica. Escuela de Biología. Centro de Investigación en Biotecnología, 2023
Keywords: Evaluación de riesgos; Consumo -- Microplásticos; Sustancias -- Plastificantes; Materiales plásticos; Especies marinas; Medio ambiente; Portadores -- Aditivos; Toxicidad -- Partículas; Partículas -- Plásticos; Risk assessment; Consumption -- Microplastics; Substances -- Plasticizers; Plastic materials; Marine species; Environment; Carriers -- Additives; Toxicity -- Particles; Particles -- Plastics; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering; Research Subject Categories::PHARMACY::Toxicology; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas